The delivery carriers and applications for Xiaobojian - Shiyu Huang; Gangliang Huang (Discover Nano)
Abstract Berberine, also known as Xiaobojian (XBJ), is a quaternary ammonium alkaloid isolated from the traditional Chinese medicine Coptis chinensis, and is the main effective ingredient for antibacterial purpose. This work systematically reviewed recent researches on XBJ in the whole range of delivery technologies. Compared with XBJ monomer administration, other forms of drug administration, such as tablets, pellets, XBJ polymer delivery system, lipid delivery system, superdeformed vesicles nanocrystallization or emulsification of XBJ and some special substances, will increase the absorption of XBJ. XBJ can be administered through various carriers, including oral administration and topical application. The importance of XBJ carrier administration is mainly reflected in wide application prospects, various pharmacological effects, and improving drug efficacy. Graphical Abstract